Sedekah kikis sifat bakhil, rapat hubungan persaudaraan - Sahrir, Muhammad Sabri (Berita Harian, 2011)
An article published in Berita Harian, discussing about the importance of 'sadaqah' to the poors and in needs, qoited by research department of Jabatan Kemajuan Islam Malaysia (JAKIM).